2002
DOI: 10.1002/jgm.311
|View full text |Cite
|
Sign up to set email alerts
|

Polybrene and interleukin‐4: two opposing factors for retroviral transduction of bone‐marrow‐derived dendritic cells

Abstract: We have defined optimal conditions to generate and transduce murine BM-derived DCs. This included: the use of protamine sulfate during exposure to retroviral infectious supernatant and the addition of IL-4 at an early stage of the culture. Nevertheless, this cytokine also induced DC maturation. These findings have potential implications in experimental gene therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…However, this difference in results may be explained by the different modalities in BM‐DC culture. He et al 11 generated BM‐DCs in the presence of IL‐4, which strongly increases the surface expression of MHCII and costimulatory molecules (CD40, CD80, CD86) in unstimulated BM‐DCs 12–14 and therefore may mask the side‐effects associated with lentiviral transduction as apparent in BM‐DCs differentiated in the presence of GM‐CSF only. The data obtained in the present study are in accordance with findings reported by Breckpot et al 10 who noted the higher expression of CD80 in lentivirally‐transduced than in mock‐tranduced BM‐DCs generated in the presence of GM‐CSF only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this difference in results may be explained by the different modalities in BM‐DC culture. He et al 11 generated BM‐DCs in the presence of IL‐4, which strongly increases the surface expression of MHCII and costimulatory molecules (CD40, CD80, CD86) in unstimulated BM‐DCs 12–14 and therefore may mask the side‐effects associated with lentiviral transduction as apparent in BM‐DCs differentiated in the presence of GM‐CSF only. The data obtained in the present study are in accordance with findings reported by Breckpot et al 10 who noted the higher expression of CD80 in lentivirally‐transduced than in mock‐tranduced BM‐DCs generated in the presence of GM‐CSF only.…”
Section: Discussionmentioning
confidence: 99%
“…On day 5 of culture, immature BM‐DCs were replated at 0.75 × 10 6 cells/0.5 ml DC medium per well (six‐well tissue culture plate; Greiner). DCs were transduced on days 5 and 6 applying each 3.5 × 10 9 viral RNA copies/well in the presence of protamin sulfate (4 µg/ml; Sigma‐Aldrich) 12 in a total volume of 2.5 ml, and plates were centrifuged (340 g for 10 min at 37 °C). DCs were washed 5 h later by replacing 1 ml of volume with fresh DC medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The achieved efficiency of transduction (38.30 ± 0.89%) can be further increased by: 1) improving the viral vector titre, for example by virion production at 32°C [ 30 ]; 2) additional concentration of the viral vector, e.g. by using magnetic nanoparticles [ 31 ] or low speed centrifugation [ 19 ]; 3) increasing transduction competence of the recipient cells, for example by phosphate starvation of the myoblasts [ 17 ] or boosting the myoblast division rate using growth factors [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that though DC generated in GM‐CSF alone were phenotypically and functionally immature, they achieve total maturation when exposed to lipopolysacharide (LPS) (27). Whereas during GVHD, LPS produced by the microbion of gastrointestinal tract can enter systemic circulation after TBI, causing the maturing of DC (28). Could predominant immature CD8 α + DC prepared by this method maintain immunosuppressive function in vivo ?…”
Section: Discussionmentioning
confidence: 99%